SERVANT LEADERSHIP OF SCHOOL ADMINISTRATORS THAT AFFECT THE EFFECTIVENESS OF SCHOOLS UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Jarupoom, Jarunee; Klinmalee, Rattaporn; Chatakan, Werayut (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to 1) study the level of service-oriented leadership of school administrators, 2) study school effectiveness, 3) study the service-oriented leadership of administrators that affects school effectiveness, and 4) study Guidelines for the development of service-oriented leadership of school administrators Nakhon Si Thammarat Primary Educational Service Area Office 2 was a quantitative and qualitative research. The samples used were 335 teachers of Nakhon Si Thammarat Primary Educational Service Area Office 2. The research tools were 2 types of questionnaires and interviews. Data were analyzed by stepwise multiple regression analysis. The results of the research were as follows: 1) service-oriented leadership of school administrators; Overall, it was at a high level. 2) Overall educational institution effectiveness at a high level 3) The service leadership of administrators that affects the effectiveness of educational institutions. Overall, there was a high level of the same direction relationship (r=.858). 4) Guidelines for the development of service-oriented leadership of school administrators In each aspect, the results were as follows. Awareness Executives should develop themselves regularly. foresight Executives can be farsighted. in order to predict future events empathetic side Should take care of him to pay attention to us. Recognize and respect the teacher’s opinions. treatment Executives must have the ability to heal themselves and others. shared responsibility Management creates meetings and exchanges of ideas. accept different ideas Persuasion Executives should express themselves so that personnel have credibility and trust. dedication to human development Administrators must devote themselves to developing teachers, developing organizations, building a community. Executives must have the ability to create a working atmosphere.